The Simultaneity of Compliance and Resistance: Buddhism, Xuyun, and the Early Communist Regime = $Lchi既顺从又抗爭 : 佛教、虛雲與五十年代的中共政权 - Ip, Hung-yok (Review of Religion and Chinese Society, 2017)
To examine the history of Chinese Buddhism in the early Communist regime, I propose to study Xuyun (虛雲, 1840–1958), one of the pre-eminent monks in modern China. I will delineate the ways in which Xuyun brought his religion in line with Marxist politics. To help Buddhism secure a place in the early People’s Republic of China, he took part in the construction of a new Buddhism compatible with socialist ideology. However, I would venture to conceptualize as resistance some of Xuyun’s efforts to preserve Buddhism. This article examines his resistance at two levels. First, while working hard to prove the value of Buddhism to the state, Xuyun mounted what can be regarded as rightful resistance. When possible, he confronted policies and authorities that hurt the sangha, but did so without challenging the legitimacy of the ccp. Second, in the 1950s, Xuyun strove to instruct Chinese Buddhists in self-cultivation. As he shared his experience and knowledge about spiritual practice with fellow Buddhists, he showed them, especially monastics, how to uphold Buddhist ideals in a political context marked by hostility towards religions.